KOMUNIKASI LEMAH LEMBUT DALAM STUDI HADITS - Hanif Hanif (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Gentleness has the virtues that adorn greetings and actions so that it can bring good and reward. The purpose of writing this article is to describe the virtues of gentleness towards fellow humans and animals based on Islamic teachings in the context of hadith studies. The writing of this article uses a library research approach. Data collection techniques are carried out by collecting data about meek communication sourced from the Koran, hadiths, commentaries, journals and relevant books. Data collected from various literatures are analyzed and analyzed so as to find a conclusion about the concept of meek communication in the context of hadith studies. Meek nature is very important to be applied in daily life both for humans and animals. Meekness is highly recommended in relationships even with people who do not do good to us. The application of a meek attitude in life will create unity and unity, prevent division and hostility and the establishment of harmonious relationships that lead to the creation of peace and social integration based on Islamic values.